The Effect of Service Quality, Perceived Ease of Use, and Perceived Usefulness on User Satisfaction of BCA Mobile Banking Application in Surabaya - Aqilah Mahda Az Zuhra; Siti Aminah; Nanik Hariyana (Universitas KH. Abdul Chalim Mojokerto, 2025)
The advancement of technology continues to simplify various aspects of human life, with mobile banking emerging as one of the most widely adopted innovations. BCA Mobile stands out as one of the leading mobile banking applications, competing closely with other platforms to maintain its position in the market. This study aims to examine the influence of service quality, perceived ease of use, and perceived usefulness on user satisfaction with BCA Mobile in Surabaya. The sample consists of 112 respondents who meet the criteria of being at least 17 years old and having used the BCA Mobile application at least once. A purposive sampling technique was used to select participants, and data were collected through a structured questionnaire. The data analysis was conducted using the Partial Least Squares (PLS) method. The findings indicate that service quality, perceived ease of use, and perceived usefulness all have a positive and significant impact on the satisfaction of BCA Mobile users in Surabaya.